2016
DOI: 10.1002/ccr3.726
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive management for iatrogenic splenic injury caused by chest tube insertion: a case report

Abstract: Key Clinical MessageSplenic injury is one of the most critical complications of chest tube insertion and often requires invasive emergency management. However, noninvasive management such as delayed removal of the malpositioned tube may be considered for a stable patient without severe adverse event.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
(14 reference statements)
0
5
0
1
Order By: Relevance
“…Potentially serious complications include injury to intrathoracic organs such as the heart, great vessels and lungs [6][7][8][9]. In addition, serious injuries can occur to structures outside the thoracic cavity such as the liver or spleen [10][11][12][13][14]. Less severe complications, such as a kinked TT or incorrect placement into lung fissures, are more common and may render pleural drainage ineffective necessitating TT replacement.…”
Section: Introductionmentioning
confidence: 99%
“…Potentially serious complications include injury to intrathoracic organs such as the heart, great vessels and lungs [6][7][8][9]. In addition, serious injuries can occur to structures outside the thoracic cavity such as the liver or spleen [10][11][12][13][14]. Less severe complications, such as a kinked TT or incorrect placement into lung fissures, are more common and may render pleural drainage ineffective necessitating TT replacement.…”
Section: Introductionmentioning
confidence: 99%
“…Indications for embolization include contrast leakage, pseudoaneurysm, Grade IV and V lesions, and hemoglobin continuous drop 3,4 ; patient hemodynamic stability is an essential condition. However, prior selective embolization and hemostatic material injection to the path during chest tube removal is an unusual technique, since in a literature review, we have only found one case that required angioembolization some days after chest drainage removal, with no knowledge of its previous malposition in the spleen 5 , and another case of conservative management with intra-splenic chest tube being left for 2 weeks and subsequently removed after the formation of a fistulous path around the tube 6 .…”
Section: Discussionmentioning
confidence: 98%
“…Proximity of the spleen to the left hemidiaphragm makes for it to be susceptible to be injured when a chest tube is inserted, especially if the "safety triangle" is not respected 9 : latissimus dorsi muscle anterior border, pectoralis major muscle lateral border, and horizontal line at the level of the nipple; sometimes, using ultrasound is necessary 6 for chest drainage correct insertion. If despite preventive measures the spleen is injured, in case of hemodynamic stability, and depending on the situation and patient characteristics, conservative management may be considered in order for future postsplenectomy sepsis or other possible complications of excisional surgery to be prevented.…”
Section: Discussionmentioning
confidence: 99%
“…Las indicaciones para la embolización son fuga de contraste, pseudoaneurisma, lesiones de grado IV y V, y descenso continuo de la hemoglobina 3,4 ; es condición imprescindible la estabilidad hemodinámica del paciente. Sin embargo, la embolización selectiva previa y la inyección de material hemostático en el trayecto durante la retirada del tubo de tórax es una técnica inusual, ya que en la revisión de la literatura solo hemos encontrado un caso que precisó angioembolización días después de la retirada del drenaje torácico, con desconocimiento de su mal posicionamiento esplénico previo 5 , y otro caso de manejo conservador con mantenimiento del tubo torácico intraesplénico durante 2 semanas y su posterior retirada tras la formación de un trayecto fistuloso alrededor del tubo 6 .…”
Section: Discussionunclassified